Franchisee failures in Malaysia: Contribution of financial and non-financial factors - Mohd Harif, Mohd Amy Azhar; Hoe, Chee Hee; Mahad Noor, Norsyema Hani (2011)
From the literature, there are 13 factors discussed to be contributed to the franchisee failure, which could be categorized into two categories, non-financial and financial factors. The non-financial factors consisted of nine factors and financial factors consisted of four factors. The non-financial factors include too rapid expansion of the franchise business, greed of franchisee, franchisee attitude, poor service, poor management of the franchise business, conflict with franchisor, legal imperfection, location and external factor. Meanwhile, financial factors looked at under capitalization of the franchisee, high overhead expenses, cash flow mismanagement and bad payers franchisee. For this individual assignment, this paper tried to determine whether the factors discussed in the literature could contributes to the franchisee failures in Malaysia. The findings may be beneficial to franchisor in selection process of franchisee and provide greater understanding between franchisor and franchisee in order to improve the performance of the franchise business.